Highly efficient removal of hexavalent chromium from electroplating wastewater using aminated wheat straw. Issue 11 (21st January 2016) - Yao, Xiaolong; Deng, Shubo; Wu, Rui; Hong, Siqi; Wang, Bin; Huang, Jun; Wang, Yujue; Yu, Gang
Abstract : Highly efficient aminated wheat straw had high adsorption and selectivity for Cr(vi ) in electroplating wastewater, and some adsorbed Cr(vi ) were reduced to Cr(iii ) and released into solution. Abstract : Highly efficient aminated wheat straw (WS) was successfully prepared by first oxidizing with nitric acid and then grafting tetraethylenepentamine (TEPA) onto WS surfaces, and the HNO3 oxidation process made more carboxyl and hydroxyl groups available for subsequent reactions. Due to the presence of lots of amine groups on the surfaces, the aminated WS exhibited positive zeta potentials at pH below 9.8 and had the sorption capacity of up to 454 mg g −1 for anionic Cr(vi ) at pH 2.2 according to the Langmuir fitting, higher than other reported adsorbents. In spite of some coexisting pollutants in the electroplating wastewater, the aminated WS still exhibited high adsorption capacity and selectivity for Cr(vi ). The spent adsorbent can be reused after regeneration and had relatively high Cr(vi ) adsorption in five cycles. Electrostatic attraction was mainly responsible for Cr(vi ) adsorption on the aminated WS. The adsorbed Cr(vi ) anions were reduced to Cr(iii ) on the adsorbent surfaces, and the formed Cr(iii ) cations were released into the solution and adsorbed on the adsorbent via chelation.